Realization of biped walking on uneven terrain by new foot mechanism capable of detecting ground surface - Hyun-jin Kang; Hashimoto, Kenji; Kondo, Hideki; Hattori, Kentaro; Nishikawa, Kosuke; Hama, Yuichiro; Hun-ok Lim; Takanishi, Atsuo; Suga, Keisuke; Kato, Keisuke (2010 IEEE International Conference on Robotics and Automation, 2010)
We have developed a new biped foot mechanism capable of detecting ground surface to realize stable walking on uneven terrain. The size of the foot mechanism is 160 mm × 277 mm and its weight is 1.5 kg. The foot system consists of four spikes each of which has an optical sensor to detect ground height. The foot makes a support polygon on uneven terrain by using three or four spikes. We have conducted several experiments on the outdoor ground surface that has a slope of 7.0 degrees and a maximum height of 15 mm bumps, and the effectiveness of the foot mechanism is confirmed.